PENGARUH PROMOSI, HARGA, MARKETING DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI PADA PT. PLANET BAN CABANG KOTA BANGKALAN - Salsa Bila; Manah Tarman; Aulia Dawam (ITB AAS Indonesia Surakarta, 2023)
Planet Ban continues to move more competitively with the increasing number of competitors which encourages Planet Ban to innovate more. One of the efforts made is to invite potential customers to visit the Planet Ban store. PT. Planet Ban implements the concept of Customer Relationship Marketing (CMR), which aims to increase long-term growth in company profitability. This research uses a case study on Planet Tire consumers with the position of PT. As Planet Ban continues to grow, it will certainly maintain its loyalty and relationship with customers. The purpose of this study is to examine the factors that can affect consumer loyalty to Planet Ban Branch, Bangkalan City by taking the theme